Rhodotor neoformans Cryptococcus , Candida albicans وضد فطرية لل Escherichia coli, Klebsiella pneumonia والسالبة لملون كرام pyogenes. , Streptococcus Staphylococcus aureus تأثير مستخلصات بعض النباتات على عدد من الجراثيم الموجبة لملون كرام - جميل ثائر العلقيسناء; أكبر علوان المياحعبدالرضا; محمد جميل علي أبو مجدادنجوى (University of Thi-Qar Journal of Science, 2019)
Antibacterial and antifungal effect of four medicinal plants extracts namely : Ocimum basillicum L , Vinca rosea L , Eruca sativa L and Nigella sativa L were tested . Three concentrations 500 mg/ml , 250 mg/ ml and 125 mg/ml of 50% water – acetic acid , alcoholic and butanolic extracts were prepared and tested against the bacteria Staphylococcus aureus , Streptococcus pyogenes , Escherichia coli and Klebsiella pneumonia , and the yeasts Candida albicans , Cryptococcus neoformans , Rhodotorula rubra and Trichosporon sp. Agar wells diffusion method was used . The results showed that the highest inhidition diameters (45.3)mm in 500 mg/ ml concentration was for the acidic water extract of Ocimum basillicum L leaves against gram positive bacteria Streptococcus pyogenes . But it was 16.3 mm for the acidic water extract of Nigella sativa L seeds against Cryptococcus neoformans . On the other hand the butanolic extracts showed highest inhibition against Escherichia coli (19.6)mm and Rhodotorula rubra (15)mm , while the butanolic extracts of Vinca rosea L had highest inhibition against Cryptococcus neoformans (12.6)mm and Streptococcus pyogenes . (21.3)mm . Alkaloids and phenolic compounds were extracted and their biological activity effect against above isolates were tested , and the results did not show any inhibitory against isolates in the three concentrations 200 mg/ ml , 100 mg/ ml and 50 mg/ ml . Also no sign for any cytotoxicity against red blood cells had been shown for all types of extracts in concentration 500 mg/ ml .